Electroanalytical determination of paroxetine in pharmaceuticals - Nouws, Henri P. A. (2013)
Electroanalytical methods based on square-wave adsorptive-stripping voltammetry (SWAdSV) and flow-injection analysis with SWAdSV detection (FIA-SWAdSV) were developed for the determination of paroxetine (PRX). The methods were based on the reduction of PRX at a mercury drop electrode at −1.55V versus Ag/AgCl, in a borate buffer of pH 8.8, and the possibility of accumulating the compound at the electrode surface. Because the presence of dissolved oxygen did not interfere significantly with the analysis, it was also possible to determine PRX using FIASWAdSV. This method enables analysis of up to 120 samples per hour at reduced costs. Both methods developed were validated and successfully applied to the quantification of PRX in pharmaceutical products.